Ethnobotanical study of Kani tribes in Thoduhills of Kerala, South India - Thangaraj Francis Xavier; Moorthy Kannan; Leyone Lija; Anthonysamy Auxillia; Antony Kanthi Freeda Rose and Subburaman Senthil Kumar (Journal of Ethnopharmacology, 2014)
Ethnopharmacological relevance: India is having a rich vegetation with a wide variety of plants, because of the extreme variations in geographical and climatic conditions prevailing in the country. Plants have been used since ancient times for the treatment of various ailments. Especially, Kani tribal communities in Thodu hills of Kerala meet their healthcare needs by using non-timber minor forest products and preparations based on traditional knowledge. They still depend on medicinal plants and most of them have a basic knowledge of medicinal plants which are used for first aid remedies, to treat cough, cold, fever, headache, poisonous bites and some simple ailments. The present study was initiated with an aim to identify traditional healers who are practicing herbal medicine among the Kani tribals in Thodu hills of Kerala, India and quantitatively document their indigenous knowledge on the utilization of medicinal plants, particularly most common ethnomedicinal plants. Methods: A field study was carried out over a period of 1 year in Thodu hills. The ethnomedicinal information was collected through interviews among the Kani traditional healers. The collected data were analyzed through use value (UV), informant consensus factor (Fic), fidelity level (FL) and relative importance (RI). Results: During the present study a total of 35 medicinal plant species belonging to 28 families and 34 genera have been documented. These plants were used to treat various diseases and ailments grouped under 14 disease categories, with the highest number of species (7) being used for liver problems, circulatory system and dermatological disorders, followed by skeleto muscular system disorders (6), and fever (5). In the study area the informant consensus about usages of medicinal plants ranges from 0.70 to 1 with an average value of 0.83. Herbs (46%) were the primary source of medicine, followed by shrubs (23%). Plumbago zeylanica (UV of 1.86) and Ocimum tenuiflorum (UV of 1.57) are the most frequently and popularly used medicinal plant species in the study area. Aristolochia tagala is rare and a vulnerable climber, Curculigo orchioides, Elephantopus scaber, Helicteres isora, Smilax zeylanica and Strychnos nux-vomica are rare species which need to be conserved for future use. Conclusion: The high degree of consensus among the informants suggests that the current use and know- ledge is still strong. The efficacy and safety of all the reported ethnomedicinal plants needs to be evaluated for phytochemical and pharmacological studies, especially the plants with high informant consensus factor, use value and fidelity level should be given priority to carry out bioassay and toxicity studies. We recommend the plants Plumbago zeylanica, Ocimum tenuiflorum, Artocarpus hirsutus, Andropogon muricatus, Helicteres isora, Coscinium fenestratum and Justicia adhatoda with high UV and RI values. Biophytum sensitivum, Curculigo orchioides, Strychnos nux-vomica, Gossypium hirsutum, Artocarpus heterophyllus, Elephantopus scaber, Pergularia daemia and Pyrrosia heterophylla (newly reported claims with highest FL) for further ethnophar- macological studies for the discovery of potential new drugs.